Artificial Intelligence, Social Media, and Post-Truth: An Islamic Education Perspective - Latifahlatifah; Khairil Anwar; Mowafg Abrahem Masuwd (Al-Mudarris, 2026)
The rapid development of Artificial Intelligence (AI) and social media has transformed the way information is produced, distributed, and consumed in contemporary society. Although previous studies have examined digital literacy and misinformation, limited research has explored the integration of Islamic educational values as a framework for addressing post-truth challenges. This study aims to analyze the relationship between AI, social media, and the post-truth phenomenon from the perspective of Islamic education. Using a qualitative library research approach, data were collected from scholarly literature and relevant Islamic sources and analyzed through thematic and normative interpretation. The findings indicate that AI-driven algorithms and social media platforms reinforce information bias through echo chambers and filter bubbles, thereby accelerating the spread of misinformation. In response, this study proposes an Islamic Digital Literacy Framework based on the principles of tabayyun (verification), shiddiq (truthfulness), and amanah (responsibility). These values provide ethical guidance for evaluating and disseminating information in digital environments. Theoretically, the study contributes to the development of Islamic education scholarship by integrating digital literacy with Islamic ethical principles. Practically, the framework offers a reference for schools, madrasahs, and other Islamic educational institutions in fostering critical, ethical, and responsible digital citizenship in the era of AI and post-truth.